Answer:
No solution
Explanation:
First you would start off by multiplying the -1 into the 2x and 4 which equals -2x and -4 then you would combine like terms on both sides. This leaves you with -1x-4=-1x-4. You would now subtract the -1 to the other side of the equal sign which leaves -4=-4 there for having no soultion
4th option
Given
- (2x + 4) + x = 3x - 4x - 4 ← simplify both sides
- 2x - 4 + x = - x - 4
- x - 4 = - x - 4
Since both sides are equal then the equation has infinitely many solutions
5.8m questions
7.5m answers